Potential Cybercrime and Prevention in the Overseas Official Travel Approval Letter - Rohmat, Aas; Ardhani Putri, Hanuring Ayu; Muhtarom, Muhammad; Ismiyanto, Ismiyanto; Febriani, Anies Fortina (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
The aim of this research is to the potential for cybercrime and its prevention in foreign official travel approval letters. The research method used is normative juridical. The data collection technique is library research. The data analysis technique is descriptive qualitative which is used in the form of an interactive analysis model. The research results show that the potential for cybercrime in foreign official travel approval letters includes hacking, identity theft, data breaches, phishing, spamming, cyber vandalism, virus writers, XML injection, security configuration errors. To prevent cybercrime, the simple web application or https://simpel.setneg.go.id has data security, namely security testing by the state cyber and password agency, a captcha feature on the simple web, one time password feature on simple phones, application of certified digital signatures. The conclusion of this research is that the potential for cybercrime in overseas official travel approval letters is increasing. Prevention solutions can include educating users, using a hacker perspective, patch systems, policies, Intrusion Detection Systems bundled with Intrusion Prevention Systems, antivirus firewalls. Legal regulatory steps to support the implementation of cybercrime prevention solutions, namely Law No. 11 of 2008 concerning ITE and PP No. 82 of 2012 concerning the implementation of Electronic Systems and Transactions.